Pengaruh Literasi Keuangan dan Kemampuan Manajerial terhadap Kinerja Keuangan Toko Bangunan Wanasari Kabupaten Brebes - Wahyu Firmansyah; Nasiruddin, Nasiruddin; Mohamad Badrun Zaman; Dumadi, Dumadi; Roni, Roni (BADAN PENERBIT STIEPARI PRESS, 2025)
This research aims to analyze the influence of financial literacy and managerial ability on the financial performance of building material stores in Wanasari District, Brebes Regency. The background of this study is based on the importance of effective financial management and good managerial skills in supporting business success, especially in the building material store sector. The research method used is a quantitative method with a survey approach. Data was collected through questionnaires distributed to owners or managers of building material stores in Wanasari District, Brebes Regency. Data analysis was carried out using multiple regression analysis to test the proposed hypotheses. The results show that financial literacy has a positive and significant influence on financial performance. Similarly, managerial ability also proved to have a positive and significant influence on financial performance. Simultaneously, financial literacy and managerial ability together significantly affect the financial performance of building material stores. These findings indicate that improving financial literacy and managerial ability among building material store owners or managers can contribute to enhancing their business's financial performance.